2007
DOI: 10.1111/j.1540-8159.2007.00593.x
|View full text |Cite
|
Sign up to set email alerts
|

Preclavicular Route Following Cephalic Venous Cutdown for Pacemaker or Defibrillator Lead Implantation

Abstract: Following cephalic venous cutdown, an unexpected preclavicular course was used in two cases for a pacemaker and a defibrillator lead implantation. This very rare anomaly was documented by cephalic venogram but did not cause any significant intraoperative difficulty during single lead implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
1
3
1
Order By: Relevance
“…Only in the case described by Trigano et al an attempt placing the electrodes was undertaken. However, this case had an anomalous cephalic course draining into the proximal subclavian vein, contrary to our case where a supraclavicular course of the cephalic vein drained into the external jugular vein; the recommendation in such cases is to leave the access and find an alternative approach to avoid lead erosion [5,6]. The cephalic vein cutdown is a safe technique to gain central venous access, preventing the well-known complication of subclavian crush syndrome.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Only in the case described by Trigano et al an attempt placing the electrodes was undertaken. However, this case had an anomalous cephalic course draining into the proximal subclavian vein, contrary to our case where a supraclavicular course of the cephalic vein drained into the external jugular vein; the recommendation in such cases is to leave the access and find an alternative approach to avoid lead erosion [5,6]. The cephalic vein cutdown is a safe technique to gain central venous access, preventing the well-known complication of subclavian crush syndrome.…”
Section: Discussioncontrasting
confidence: 75%
“…Once it crosses the elbow at the antecubital fossa, it moves towards the lateral aspect of the biceps and at the proximal third of the arm dives in between the pectoralis major and deltoid muscles, joining the axillary vein just inferior to the clavicle [1,2]. Anatomical studies have documented variations in the course of the cephalic vein, but the clinical cases reported in medical literature are rare, and include cases with absence or small diameter of the cephalic vein, accessory veins running parallel to the cephalic vein or even pre-clavicular or supraclavicular anomalous courses (<1% of all dissection series, accounting for less than five reported cases in the medical literature) [3][4][5][6]. Only in the case described by Trigano et al an attempt placing the electrodes was undertaken.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the classification, Kameda et al [13] suggested each frequency of subtypes as 0.4%, 1.2%, 0.4%, and 0.2%, respectively. They suggested single case report related with the variations [1,5,14,15,21,23,25,33,35] and we found some more case reports related with this variation: three for subtype 1A [2,8,12], three for subtype 1B [19,27], and one for subtype 2A [9]. The case 1 and 2 belong to subtype 1B and 1A, respectively.…”
Section: Discussionsupporting
confidence: 56%
“…The percentage of each CV type and subtype in all the reported cases is listed in Values represent frequencies and percentages. All the percentages were rounded to the nearest whole number [1,2,3,4,5,6,7,8,9,10,13,14,17,18,19,20,22,25].…”
Section: Resultsmentioning
confidence: 99%